The Covid-19 Pandemic Crisis and the Technological Revolution - Protasiewicz Anna; Zalesko Elżbieta (Studies in Logic, Grammar and Rhetoric, 2023)
The aim of this article is to present the changes referred to as the “fourth industrial revolution” and the role of the crisis caused by the COVID-19 pandemic in accelerating the technological revolution in relation to Polish companies. The ongoing economic downturn has different causes and much broader effects than previous crises. Hence the need to analyze trends (megatrends) in the emergence of innovations initiated or significantly accelerated by the pandemic crisis, and consequently, among other things, the intensification of the digital transformation process.